2015
DOI: 10.1016/j.nmd.2015.06.432
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of neuralgic amyotrophy (Parsonage–Turner syndrome) in a primary care setting: A prospective cohort study

Abstract: ObjectiveNeuralgic amyotrophy is considered a rare peripheral nervous system disorder but in practice seems grossly under recognized, which negatively affects care for these patients. In this study we prospectively counted the one-year incidence rate of classic neuralgic amyotrophy in a primary care setting. MethodsIn a prospective cohort study during the year 2012 we registered all new cases of neck, shoulder or arm complaints from two large primary care centers serving a population of 14,118. Prior to study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 13 publications
2
57
1
9
Order By: Relevance
“…For NA we calculated an incidence of 18/10 000 person years. This is considerably higher than 1‐3/100 000 person years that is historically found in the literature, but lower than recent prospective research showed after training of general practitioners in the general population (up to 1/1000 person years) . As military personnel and military doctors are not trained to recognize NA, we think our incidence of NA is still an underestimation and might be even higher than in the general population.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…For NA we calculated an incidence of 18/10 000 person years. This is considerably higher than 1‐3/100 000 person years that is historically found in the literature, but lower than recent prospective research showed after training of general practitioners in the general population (up to 1/1000 person years) . As military personnel and military doctors are not trained to recognize NA, we think our incidence of NA is still an underestimation and might be even higher than in the general population.…”
Section: Discussioncontrasting
confidence: 59%
“…Neuralgic amyotrophy is a clinically defined syndrome characterized by acute onset, severe pain in the shoulder and/or upper arm(s), with subsequent multifocal peripheral nervous system symptoms that can be bilateral but are always asymmetric. Criteria for this disorder have been described in previous publications …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that HEV3 causes a specific phenotypic variant of neural gic amyotrophy with these features. Recent data suggest that the incidence of neuralgic amyotrophy in primary care could be as high as 1 per 1,000 per year, which is 30-50 times more frequent than previously thought 92 . The prevalence of HEV among milder cases of neuralgic amyotrophy remains an open question.…”
Section: Pathogenesismentioning
confidence: 84%
“…[4][5][6] In brief, NA is a relatively rare disorder (1-year incidence 1-3 per 100,000 in a 1985 Minnesota study 7 ; 1-year incidence 1/1000 individuals in a 2015 the Netherlands study 8 ). Although classically a brachial plexus affliction, NA may involve other nerves.…”
Section: Discussionmentioning
confidence: 99%